1998
DOI: 10.1111/j.1572-0241.1998.300_s.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Angiomyolipoma: A Previously Undescribed Cause of Upper Gi Hemorrhage

Abstract: Angiomyolipomas are rare lesions often arising in the kidney. We describe the first documented case of symptomatic gastric angiomyolipoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A review of the literature yielded only three previously reported cases of AML in the gastrointestinal tract, but all of these were of the conventional morphologic type [24][25][26] (Table 2). They presented as submucosal masses measuring up to 3 cm in size, leading in two instances to ulceration of the overlying mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature yielded only three previously reported cases of AML in the gastrointestinal tract, but all of these were of the conventional morphologic type [24][25][26] (Table 2). They presented as submucosal masses measuring up to 3 cm in size, leading in two instances to ulceration of the overlying mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Focally, melanin pigment was present in the cytoplasm of the tumor cells. Immunohistochemically, the tumor [26] 50 M Descending colon 3 cm pedunculated & ulcerated polyp Conventional Helwig et al, 1998 [24] 75 F Stomach 1.2 cm submucosal ulcerated mass Conventional This report, Case 1 6 F Appendix 1.3 cm transmural and intraluminal mass Pleomorphic This report, Case 2 22 F Cecum 3 cm transmural mass Pleomorphic cells were strongly positive for vimentin and HMB-45; focally positive for smooth muscle actin, desmin, and A103; and negative for the other markers tested (Figs. 8, 9, Table 1).…”
Section: Casementioning
confidence: 99%
“…Only few reports of the occurrence of extra-renal AML in the colon, stomach, and small bowel have been published. [13,[26][27][28][29] However, no reports of NF1 being accompanied by AML have been published, with only 1 case of renal AML reported to occur in segmental neurofibromatosis. [14] AML is a tumor composed of varying proportions of mature adipocytes, smooth muscle, and irregular blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The unifying concept of a family of lesions characterized by the presence of perivascular epithelioid cells has been suggested (17). A review of the literature revealed three previously reported cases of angiomyolipoma in the gastrointestinal tract (18)(19)(20). They presented as submucosal masses measuring up to 3 cm, leading, in two instances, to ulceration of the overlying mucosa.…”
Section: Discussionmentioning
confidence: 99%